Re-ethnization and Legitimation of Kankuamo Indigenous in Identity Discourses (2020)
This article aims to describe the characteristics of the process of re-ethnization of the Kankuamo Indigenous of Cesar state, through the speeches of the actors who participated in the process. These discourses represent scenarios of legitimacy since they are arranged as an instrument of political and administrative recognition, establishing relationships in hegemonic and domination spaces. The analysis is proposed from a documentary sources review, such as ethnological studies that supported such institutional recognition, documents and audiovisual records of the Kankuamo Reservation that are part of the process memory. The political nature of ethnic recovery is discussed, and it is established that the speech appears as a device that materializes in social reproduction through the mechanisms of legitimation such as territory, identity or indigenity..